Seismic design optimization of multi–storey steel–concrete composite buildings. (1st July 2016) - Papavasileiou, Georgios S.; Charmpis, Dimos C.
Highlights: A complete framework for seismic design optimization of composite buildings is presented. Buildings have: steel HEB-columns encased in concrete; steel IPE-beams; steel L-bracings. Member capacities are checked according to Eurocodes 3 and 4. Seismic system performance is checked using nonlinear pushover and eigenvalue analysis results. Cost-effective structural designs are identified using a discrete evolutionary optimization algorithm. Abstract: This work presents a structural optimization framework for the seismic design of multi–storey composite buildings, which have steel HEB-columns fully encased in concrete, steel IPE-beams and steel L-bracings. The objective function minimized is the total cost of materials (steel, concrete) used in the structure. Based on Eurocodes 3 and 4, capacity checks are specified for individual members. Seismic system behavior is controlled through lateral deflection and fundamental period constraints, which are evaluated using nonlinear pushover and eigenvalue analyses. The optimization problem is solved with a discrete Evolution Strategies algorithm, which delivers cost-effective solutions and reveals attributes of optimal structural designs.